The Effect of Empowering Health Cadres Through Whatsapp on the Knowledge and Skills of Health Cadres in Hypertension Management - Maitha Annthonette Wulan Keloay; Ferry Efendi; Makhfudli Makhfudli; Retno Indrawati; Andri Setiya Wahyudi; Elida Ulfiana (Indonesian Journal of Global Health Research, 2026)
Hypertension remains one of the leading causes of global mortality, affecting approximately 1.28 billion adults worldwide, yet only 21% successfully manage to control their blood pressure. This highlights the urgent need for community-based strategies, particularly through the empowerment of health cadres. Digital health education interventions—such as those utilizing WhatsApp—are considered promising for enhancing cadres’ competencies in hypertension management. The aim of this study was to determine the effect of empowering health cadres through Whatsapp on the knowledge and skills of cadres in hypertension management. This study employed a quasi-experimental design with a pretest-posttest control group approach. The first phase involved the development of a training module informed by a literature review, field study, and expert consultation. Data collection was done using purposive sampling with inclusion and exclusion criteria, a total of 60 respondents, 30 intervention and control groups each. In the second phase, an intervention was conducted involving 60 health cadres (30 in the intervention group and 30 in the control group) within the jurisdiction of Tateli public health care, delivered via WhatsApp. Data were analyzed using the Wilcoxon Signed Rank Test and the Mann-Whitney U Test, with a significance level set at p < 0.05. The findings revealed a statistically significant improvement in both knowledge and skills among cadres in the intervention group. Knowledge increased from moderate (90%) to good (73.3%), and skills from moderate (90%) to good (93.3%), with p < 0.001. No significant changes were observed in the control group. WhatsApp-based educational interventions are effective in improving health cadres' knowledge and skills in hypertension management. Given its accessibility, affordability, and practicality, WhatsApp serves as a strategic and sustainable tool for ongoing cadre training in the prevention and control of non-communicable diseases at the community level.